2018
DOI: 10.1038/s41377-018-0101-2
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic microscopy at multiple discrete frequencies

Abstract: Optoacoustic (photoacoustic) sensing employs illumination of transient energy and is typically implemented in the time domain using nanosecond photon pulses. However, the generation of high-energy short photon pulses requires complex laser technology that imposes a low pulse repetition frequency (PRF) and limits the number of wavelengths that are concurrently available for spectral imaging. To avoid the limitations of working in the time domain, we have developed frequency-domain optoacoustic microscopy (FDOM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…We next tested the optical and OA characteristics of C 70 @lysozyme to investigate its potential as a contrast agent for phototheranostics. Using a custom‐built hybrid microscopy system, [ 68–73 ] which combines optical‐resolution OA, THG, and 2PEF microscopy, we clearly demonstrated that C 70 generates significant THG response (Figure S9A, Supporting Information) as well as intense OA signal (Figure S9B, Section S9, Supporting Information) when dispersed on a microscope slide.…”
Section: Resultsmentioning
confidence: 99%
“…We next tested the optical and OA characteristics of C 70 @lysozyme to investigate its potential as a contrast agent for phototheranostics. Using a custom‐built hybrid microscopy system, [ 68–73 ] which combines optical‐resolution OA, THG, and 2PEF microscopy, we clearly demonstrated that C 70 generates significant THG response (Figure S9A, Supporting Information) as well as intense OA signal (Figure S9B, Section S9, Supporting Information) when dispersed on a microscope slide.…”
Section: Resultsmentioning
confidence: 99%
“…It sensed a broad variety of biologically relevant compounds, e.g. vasculature, collagen, elastin, keratinocytes, hair follicle, sebaceous glands, and lipid embeddings [2,7,[10][11][12]. This allowed us to study small model organisms such as fish larvae and mouse ears in vivo (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another future perspective of PA diagnosis in CH is the development of low-cost, compact systems integrating cheap excitation sources with high wavelength availability ranging from near UV to mid-IR, such as Light Emitting Diodes (LEDs) and diode lasers. These light sources could be directly modulated using digital or analog intensity modulation schemes to produce light pulses in the order of ns [64], or variable intensities with frequencies found in the MHz regime [65]. The intensity-modulation of low-cost sources could essentially overcome wavelength limitations of commonly used Q-Switched lasers, enabling multispectral PA imaging capabilities and potential differentiation of optical absorbers through specialized spectral unmixing algorithmic procedures [66].…”
Section: Discussionmentioning
confidence: 99%